FORTIFICATION OF NANO CALCIUM OF FRESHWATER MUSSEL SHELL (Pilsbryoconcha exilis) FLOUR ON THE HEDONIC QUALITY OF PLAIN BREAD - Legia Ayu Gustina; N. Ira Sari; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT This study aims to determine the effect of fortification of nano calcium freshwater mussel shell flour on the hedonic quality of plain bread. The treatment given was fortification of nano calcium of freshwater mussel on plain bread, consisting of R0 (0%), R1 (0.5%), R2 (1%), and R3 (1.5%). The analysis parameters observed were hedonic quality (appearance, aroma, taste, texture). Based on the result found that the best treatment was 1% fortification (5 g of nano calcium of freshwater mussel shell flour) with visual characteristics, namely intact appearance, inner color of creamy plain bread and brownish yellow outer color, fragrant aroma, tasteless and savory taste, and smooth / soft texture. Keywords: plain bread, nano calcium of freshwater mussel shell flour, fortification